Anti-Inflammatory Effects of Agrimoniin-Enriched Fractions of Potentilla erecta - Julia Hoffmann; Federica Casetti; Ute Bullerkotte; Birgit Haarhaus; Jan Vagedes; Christoph M. Schempp; Ute Wölfle (Molecules, 2016)
Potentilla erecta (PE) is a small herbaceous plant with four yellow petals belonging to the Rosaceae family. The rhizome of PE has traditionally been used as an antidiarrheal, hemostatic and antihemorrhoidal remedy. PE contains up to 20% tannins and 5% ellagitannins, mainly agrimoniin. Agrimoniin is a hydrolyzable tannin that is a potent radical scavenger. In this study we tested the anti-inflammatory effect of four PE fractions with increasing amounts of agrimoniin obtained by Sephadex column separation. First, we analyzed in HaCaT keratinocytes the expression of cyclooxygenase-2 (COX-2) induced by ultraviolet-B (UVB) irradiation. As COX-2 catalyzes the metabolism of arachidonic acid to prostanoids such as PGE2, we also measured the PGE2 concentration in cell culture supernatants. PE inhibited UVB-induced COX-2 expression in HaCaT cells and dose-dependently reduced PGE2. The PE fraction with the highest agrimoniin amount (PE4) was the most effective in this experiment, whereas fraction PE1 containing mainly sugars had no effect. PE4 also dose dependently inhibited the phosphorylation of the epidermal growth factor receptor (EGFR) which plays a crucial role in UVB-mediated COX-2 upregulation. A placebo-controlled UV-erythema study with increasing concentrations of PE4 demonstrated a dose dependent inhibition of UVB-induced inflammation in vivo. Similarly, PE4 significantly reduced UVB-induced PGE2 production in suction blister fluid in vivo. In summary, PE fractions with a high agrimoniin content display anti-inflammatory effects in vitro and in vivo in models of UVB-induced inflammation.